Integrating seismic attributes and rock physics for delineating Pliocene reservoir in Disouq field, Nile Delta, Egypt - HESHAM, Ahmed; FATTAH, Nadia Abdel; DAHROUG, Aia (Contributions to Geophysics and Geodesy, 2023)
The Nile Delta is known as the most prolific gas province in North Africa. Gas exploration and production were the main targets over decades in the Nile Delta. The integration of petrophysical analysis, seismic interpretation, and seismic attributes could indicate the presence of gas in Disouq field, which is located in Nile Delta, Egypt. Well log data showed that the reservoir is classified into three zones (A, B, and C). These zones are characterized by low gamma ray (around 35%), with relatively high porosity (around 29%) and low water saturation (36–38%). Structural and stratigraphic interpretation was conducted in order to investigate the extension and geometry of the reservoir, in addition to the faults affecting the study area. The reservoir is represented by a channel of Pliocene age, characterized by the low impedance sand saturated by gas. Near and far offset data show the gas effect. There is an increase of the negative amplitude from near to far offset. The amplitude map and structural contours match well and show good conformance. Seismic attributes including surface attributes and “Red Green Blue/colour blending” help in delineating the extent and geometry of the reservoir, in addition to the possible prospect. Finally, the volume of original gas in place was estimated what showed that the study area is of great economic interest.